Computer Highlights Society Magazines. (Computer (00189162), 2009)
The article presents highlights of recent issues of IEEE Computer Society magazines including an article in the January 2009 issue of "Software" about software development, an article about energy use by computers in an issue of "IT Professional," and articles about exploring high-level synthesis in the July/August 2009 issue of "Design & Test."